Synthesis, Anticancer Activity on Prostate Cancer Cell Lines and Molecular Modeling Studies of Flurbiprofen-Thioether Derivatives as Potential Target of MetAP (Type II) - KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (BENTHAM SCIENCE PUBL LTD, 2020)
Background: Prostate cancer is still one of the serious causes of mortality and morbidity in men. Despite recent advances in anticancer therapy, there is a still need of novel agents with more efficacy and specificity in the treatment of prostate cancer. Because of its function on angiogenesis and overexpression in the prostate cancer, methionine aminopeptidase-2 (MetAP-2) has been a potential target for novel drug design recently. Objective: A novel series of Flurbiprofen derivatives N-(substituted)-2-(2-(2-fluoro-[1,1'-biphenyl]-4-il)propanoyl)hydrazinocarbothioamide (3a-c), 4-substituted-3 -(1 -(2-fluoro-[1,1'-biphenyl]-4-yl)ethyl)-1H-1,2,4-triazole-5(4H)-thione (4a-d), 3-(substitutedthio)-4-(substituted-pheny1)5-(1-(2-fluoro-[1,1'-biphenyt]-4-yl)ethyl)-411-1,2,4-triazole (5a-y) were synthesized. The purpose of the research was to evaluate these derivatives against MetAP-2 in vitro and in silico to obtain novel specific and effective anticancer agents against prostate cancer. Methods: The chemical structures and purities of the compounds were defined by spectral methods (H-1-NMR, C-13-NMR, HR-MS and FT-IR) and elemental analysis. Anticancer activities of the compounds were evaluated in vitro by using MTS method against PC-3 and DU-143 (androgenindependent human prostate cancer cell lines) and LNCaP (androgen-sensitive human prostate adenocarcinoma) prostate cancer cell lines. Cisplatin was used as a positive sensitivity reference standard. Results: Compounds 5b and 5u; 3c, 5b and 5y; 4d and 5o showed the most potent biological activity against PC3 cancer cell line (IC50 = 27.1 mu M, and 5.12 mu M, respectively), DU-145 cancer cell line (IC50 - 11.55 mu M, 6.9 mu M and 9.54 mu M, respectively) and LNCaP cancer cell line (IC50 - 11.45 mu M and 26.91 mu M, respectively). Some compounds were evaluated for their apoptotic caspases protein expression (EGFR/PI31C/AKT pathway) by Western blot analysis in androgen independent-PC3 cells. BAX, caspase 9, caspsase 3 and anti-apoptotic BcL-2 mRNA levels of some compounds were also investigated. In addition, molecular modeling studies of the compounds on MetAP-2 enzyme active site were evaluated in order to get insight into binding mode and energy. Conclusion: A series of Flurbiprofen-thioether derivatives were synthesized. This study presented that some of the synthesized compounds have remarkable anticancer and apoptotic activities against prostate cancer cells. Also, molecular modeling studies exhibited that there is a correlation between molecular modeling and anticancer activity results.
Keywords: EGFR/PI3K/AKT pathway; LNCaP; flurbiprofen; thioether; methionine aminopeptidase; prostate cancer; METHIONINE AMINOPEPTIDASE-2 INHIBITOR; ANTI-HCV; PROGRESSION; FUMAGILLIN; TNP-470